(untitled) (Bangladesh Journal of Medical Science, 2025)
Background Sleep habits in children with Autism Spectrum Disorder (ASD) are poorly understood despite their significant impact on overall well-being. This study aimed to comprehensively assess sleep behaviors and challenges faced by children diagnosed with ASD in Taif City, targeting individuals under 15 years old. Methodology A cohort of 130 participants, including 41 autistic children and 89 typically developing controls, was recruited using convenience and snowball sampling. Data collection involved analyzing bedtime and wake-up patterns, sleep duration, and specific sleep-related issues. Statistical analyses compared findings between the two groups. Results Autistic children exhibited distinct sleep behavior patterns compared to controls. They showed earlier bedtimes, consistent wake-up times—often earlier than controls— and notably shorter sleep durations (p<0.05). Additionally, autistic children reported significantly higher incidences of snoring and waking up with headaches, indicative of potential sleep disturbances (p<0.05).. Heightened daytime fatigue and a propensity to fall asleep during activities were also observed among autistic children. Conclusion The results show that youngsters in Taif City with autism spectrum disorder (ASD) and their normally developing classmates have very different sleeping habits. In order to enhance the overall quality and well-being of people with ASD, it is necessary to implement focused treatments that address particular difficulties linked to sleep. BJMS, Volume: 24. Supplementary Issue 2025, Page : 123-132